2021
DOI: 10.1182/blood-2021-152331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of the Drepaglobe Trial for Sickle Cell Disease Patients

Abstract: In sickle cell disease (SCD), the β6 Glu→Val substitution leads to sickle hemoglobin (HbS) polymerization and red blood cell (RBC) sickling. Transplantation of autologous, genetically modified hematopoietic stem/progenitor cells (HSPCs) represents a promising therapeutic option for patients lacking a compatible donor. We previously designed a lentiviral vector (βAS3 LV) expressing a potent anti-sickling βAS3 globin and demonstrated its safety and efficacy in SCD patient cells (Weber et al., 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The clinical product, LentiGlobin BB305 (Figure 1B), entails autologous HSCs transduced with an LV that encodes an anti-sickling variant of β-globin, known as βA-T87Q (mimicking the inhibitory effect of HbF on HbS polymerization). The recently published results confirmed stable βA-T87Q expression upon engraftment as well as reduced hemolysis, absence of VOC, and transfusion-independency (13,14). A phase III clinical study (NCT04293185) with 35 SCD patients as well as a long-term follow-up study (NCT04628585) were opened in 2020.…”
Section: Gene Therapy For Scdmentioning
confidence: 68%
“…The clinical product, LentiGlobin BB305 (Figure 1B), entails autologous HSCs transduced with an LV that encodes an anti-sickling variant of β-globin, known as βA-T87Q (mimicking the inhibitory effect of HbF on HbS polymerization). The recently published results confirmed stable βA-T87Q expression upon engraftment as well as reduced hemolysis, absence of VOC, and transfusion-independency (13,14). A phase III clinical study (NCT04293185) with 35 SCD patients as well as a long-term follow-up study (NCT04628585) were opened in 2020.…”
Section: Gene Therapy For Scdmentioning
confidence: 68%
“…Gene therapy broadly takes a variety of approaches including addition of a helpful gene, often using a lentiviral vector, gene knockdown (e.g., BCL11A silencing), direct globin gene editing to rectify the mutation (changing the HbS-encoding gene to HbA-encoding gene), and gene editing of elements that regulate globin, to at least partially reverse the normal hemoglobin switching from HbF to HbA (e.g., by targeting the BCL11A gene) [ 193 , 194 ]. Recently published pilot studies have shown that single treatment using gene therapy techniques results in sustained production of HbA in most RBCs and increased total Hb and HbF levels, reduces hemolysis, and completely resolves severe vaso-occlusive events [ 195 , 196 ], whereas variable findings have been documented in other studies [ 197 , 198 ]. Several other pilot studies are underway to primarily assess the feasibility, safety, and efficacy of gene therapy in patients with severe SCD [ 198 – 200 ].…”
Section: Other Potential and Futuristic Therapiesmentioning
confidence: 99%
“…Though 2/3 patients received treatment benefits, therapeutic amelioration correlated with VCN, reflective of engraftment capability. Patient 3 remained transfusion dependent due to low VCN and <3.0% therapeutic Hb [ 73 ]. A different study out of the University of California, Los Angeles, is using the β AS3 -FB carrying the β AS3 -globin gene and including an enhancer-blocking insulator in the 3′LTR (the footprint II (FII) of chicken HS4 insulator and human T-cell receptor blocking element alpha/delta 1 (BEAD-1) insulator).…”
Section: Hsc-targeted Gene Therapy With Lentiviral Gene Addition In Scdmentioning
confidence: 99%